Metaphors and Similes in Peter Lerangis' Novel The Curse of the King - Tri Arie Bowo; Didit Kurniadi; Donal Fernado Lubis (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
This study aims to reveal the writing style in the novel The Curse of the King by Peter Lerangis, especially in its figurative speech namely metaphor and simile. The classification of metaphors analyzed uses Newmark's classification and the simile classification used in this study is the classification described by Fromilhague. A qualitative method was used to answer the problem of the study. The research showed that there were thirteen metaphors and fifty-two similes. The metaphor compositions found were one Dead Metaphor, two Recent Metaphors, Three Stock metaphors, seven Original Metaphors, and no Cliche Metaphors. The similes found were five Explicit Similes and forty-seven Implicit Similes. Metaphors and similes in the novel use many popular references such as the words of Donald Trump, party guest, Children of the Corn, Velcro, Ninja, props in a movie, Soprano, Pizza, Flashmob, a dancer on steroids, Looney Tunes, and ET. The combination of past history with a writing style that uses popular figures of speech becomes an interesting mix that makes the novel gain many fans in the world. The novelty of this type of research is still very broad, especially in research on new words in historical fiction such as in the work of Peter Lerangis.